Odpowiedzi

  • Użytkownik Zadane
2010-02-08T17:34:45+01:00
E)
(3x-1):5 + (2y-3):4 = [3(y+1)]:2 / * 20
(x+y):4 - (3y-1):2 = (x-6y):4 / * 4

4(3x - 1) + 5(2y - 3) :4 = 10[3y+3]
x+y - 2(3y-1) = x-6y

12x - 4 + 10y - 15 = 30y + 30
x + y - 6y + 2 = x - 6y

12x - 30y + 10y = 15 + 30 + 4
x - x + y - 6y + 6y = -2

12x - 20y = 49
y = -2

12x - 20y = 49 [odstawiasz za y]
12x - 20 * (-2) = 49
12x = 49 - 40
12x = 9 /:12
x = 9/12
x = ¾

x = ¾
y=2



f)
(3x - 2):3 - (2x - y):6 = x + 1/6
x + y -(-x + y):5 = 1/5 - 0,8

(3x - 2):3 - (2x - y):6 = x + 1/6 / * 6
x + y -(-x + y):5 = 1/5 - 4/5 / * 5

2(3x - 2) - (2x - y) = 6x + 1
5x + 5y -(-x + y) = 1 - 4

6x - 4 - 2x + y = 6x + 1
5x + 5y + x - y = 1 - 4

-2x + y = 1 + 4
6x + 4y = -3

-2x + y = 5 / * 3
6x + 4y = -3

-6x + 3y = 15
6x + 4y = -3 +
___________
7y = 12 /:7
y = 12/7
y = 1 5/7




8 3 8